FORMATION OF A MODEL OF PATRIOTIC EDUCATION OF STUDENTS IN THE EDUCATIONAL ENVIRONMENT OF THE HIGHER MILITARY EDUCATIONAL INSTITUTION - Каменюк, Ю. (Київський національний університет імені Тараса Шевченка, 2021)
The article highlights the process of development and substantiation of the model of patriotic education of cadets in the educational environment of a higher military educational institution, which consists of five interrelated components: target; diagnostic; design; organizational; control and evaluation. The model was developed taking into account the requirements of system, activity, axiological, historical and diagnostic approaches. A component-by-component description of the model is made and the directions of further research are outlined. The target block determines the main purpose of patriotic education of cadets. The diagnostic block highlights the procedure for conducting a confirmatory experiment and methods of studying the level of patriotism of servicemen. The design block of the formed model is intended for creation of psychological and pedagogical conditions of formation of patriotism of cadets, and also for development of necessary tools. The result of the design block is the Target program for the formation of patriotism of servicemen "Patriot of Ukraine". The organizational unit shows the procedure for carrying out the activities of the Target Program. The control and evaluation unit of the model was formed in order to organize control, evaluation of results and further correction of the Target Program for the formation of patriotism in cadets. For a qualitative assessment of the measures, a system of criteria and indicators of patriotism has been defined and described. It is emphasized that the most important achievement of the proposed model is the integrity of information on the process of forming the patriotism of cadets. The directions of further researches, which consist in carrying out research and experimental work on formation of patriotism of servicemen and approbation of the Target program of formation of patriotism of servicemen "Patriot of Ukraine" in educational process of higher military educational institution are defined.

Висвітлено процес розробки й обґрунтування моделі патріотичного виховання курсантів в освітньому середовищі ВВНЗ, що складається із п'яти взаємопов'язаних компонентів: цільового; діагностичного; проєктувального; організаційного; контрольно-оціночного. Розробку моделі здійснено з урахуванням вимог системного, діяльнісного, аксіологічного, історичного та діагностичного підходів. Здійснено покомпонентний опис моделі й окреслено напрями подальших досліджень. Цільовий блок визначає головну мету патріотичного виховання курсантів. У діагностичному блоці висвітлено порядок проведення констатуючого експерименту та методики дослідження рівня патріотизму військовослужбовців. Проєктувальний блок сформованої моделі призначено для створення психолого-педагогічних умов формування патріотизму курсантів, а також для розробки необхідного інструментарію. Результатом проєктувального блоку є цільова програма формування патріотизму військовослужбовців "Патріот України". Організаційний блок показує порядок проведення заходів цільової програми. Контрольно-оціночний блок моделі сформовано для організації контролю, оцінки результатів та подальшої корекції цільової програми формування патріотизму у курсантів. Для якісної оцінки заходів визначено систему критеріїв та показників патріотизму, здійснено їхній опис. Наголошено, що найважливішим здобутком пропонованої моделі є цілісність подання інформації про процес формування патріотизму курсантів. Визначено напрями подальших досліджень, що полягають у проведенні дослідно-експериментальної роботи із формування патріотизму військовослужбовців та апробації цільової програми формування патріотизму військовослужбовців "Патріот України" в освітньому процесі ВВНЗ.
ПСИХОЛОГІЧНІ АСПЕКТИ ФОРМУВАННЯ МОДЕЛІ ПАТРІОТИЧНОГО ВИХОВАННЯ КУРСАНТІВ В ОСВІТНЬОМУ СЕРЕДОВИЩІ ВИЩОГО ВІЙСЬКОВОГО НАВЧАЛЬНОГО ЗАКЛАДУ
Keywords: model; patriotic education; system approach; activity approach; axiological approach; culturological approach; program; criteria; indicators; модель; патріотичне виховання; системний підхід; діяльнісний підхід; аксіологічний підхід; культурологічний підхід; програма; критерії; показники